Variation in hospital resource use and cost among surgical procedures using topical absorbable hemostats - Martyn D; Meckley LM; Miyasato G; Lim S; Riebman JB; Kocharian R; Scaife JG; Rao Y; Corral M (Dove Medical Press, 2015)
Derek Martyn,1 Lisa M Meckley,1 Gavin Miyasato,1 Sangtaeck Lim,2 Jerome B Riebman,3 Richard Kocharian,3 Jillian G Scaife,1 Yajing Rao,1 Mitra Corral2 1Trinity Partners, LLC, Waltham, MA, USA; 2Global Health Economics and Market Access, Ethicon, Inc., Bridgewater, NJ, USA; 3Medical Affairs, Ethicon, Inc., Bridgewater, NJ, USA Background: Adjunctive hemostats are used to assist with the control of intraoperative bleeding. The most common types are flowables, gelatins, thrombins, and oxidized regenerated celluloses (ORCs). In the US, Surgicel® products are the only US Food and Drug Administration-approved ORCs. Objective: To compare the outcomes of health care resource utilization (HRU) and costs associated with using ORCs compared to other adjunctive hemostats (OAHs are defined as flowables, gelatins, and topical thrombins) for surgical procedures in the US inpatient setting. Patients and methods: A retrospective, US-based cohort study was conducted using hospital inpatient discharges from the 2011–2012 calendar years in the Premier Healthcare Database. Patients with either an ORC or an OAH who underwent a cardiovascular procedure (valve surgery and/or coronary artery bypass graft surgery), carotid endarterectomy, cholecystectomy, or hysterectomy were included. Propensity score matching was used to create comparable groups of ORC and OAH patients. Clinical, economic, and HRU outcomes were compared. Results: The propensity score matching created balanced patient cohorts for cardiovascular procedure (22,718 patients), carotid endarterectomy (10,890 patients), cholecystectomy (6,090 patients), and hysterectomy (9,348 patients). In all procedures, hemostatic agent costs were 28%–56% lower for ORCs, and mean hemostat units per discharge were 16%–41% lower for ORCs compared to OAHs. Length of stay and total procedure costs for patients treated with ORCs were lower for carotid endarterectomy patients (0.3 days and US$700) and for cholecystectomy patients (1 day and US$3,350) (all P<0.001). Conclusion: Costs and HRU for patients treated with ORCs were lower than or similar to patients treated with OAHs. Proper selection of the appropriate hemostatic agents has the potential to influence clinical outcomes and treatment costs. Keywords: hemostatics, hemostatic techniques, blood transfusion, health care costs, surgical blood loss